2004
DOI: 10.1248/bpb.27.422
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Esculetin on Melanin Biosynthesis

Abstract: Coumarins are widely distributed in plants and are especially abundant in the bark, leaves, and roots of Umbelliferae and Rutaceae plants. So far more than 1300 types of coumarin have been identified as natural or synthesized compounds. Coumarins have recently been reported to have interesting pharmacologic and biochemical properties such as antioxidative, 1,2) antiinflammatory, and antiallergic effects, 3,4) inhibition of platelet aggregation 5) and protein kinase, 6) induction of apoptosis, 7) and antiviral,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 17 publications
(24 reference statements)
1
42
1
Order By: Relevance
“…Kaneko and colleagues [2] found that aesculetin and its 6-glycoside, aesculin, can inhibit oxidative DNA damage and formation of aberrant crypt foci and tumors. Further more, this compound shows an inhibitory effect on BOP-induced oxidative DNA damage and carcinogenesis in a hamster pancreatic tumor model [2] , as well as chemo-preventive [3] and anti-tumor activity on cancer [4] . Aesculin and aesculetin have strong antioxidative and photo-protective activities, by scavenging 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radicals and superoxide anions from the xanthine/xanthine oxidase system and inhibiting oxidation of 5-(6-)-chloromethyl-2', 7'-dichlorodihydro-fluorescein diacetate [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Kaneko and colleagues [2] found that aesculetin and its 6-glycoside, aesculin, can inhibit oxidative DNA damage and formation of aberrant crypt foci and tumors. Further more, this compound shows an inhibitory effect on BOP-induced oxidative DNA damage and carcinogenesis in a hamster pancreatic tumor model [2] , as well as chemo-preventive [3] and anti-tumor activity on cancer [4] . Aesculin and aesculetin have strong antioxidative and photo-protective activities, by scavenging 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radicals and superoxide anions from the xanthine/xanthine oxidase system and inhibiting oxidation of 5-(6-)-chloromethyl-2', 7'-dichlorodihydro-fluorescein diacetate [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The FT-IR spectra were recorded with Shimadzu FTIR-8400S spectrometer (Kyoto, Japan, u, cm À1 ). The 1 H NMR and 13 C NMR spectra (CDCl 3 ) and (DMSO-d 6 ) were recorded using a Bruker 400 MHz spectrometer. Chemical shifts () are reported in ppm downfield from the internal standard tetramethylsilane (TMS).…”
Section: Methodsmentioning
confidence: 99%
“…The coumarins are especially abundant in the Umbelliferae and Rutaceae families 13 and also found in higher plants where they originate from phenylpropanoid pathway 14 . Some coumarins from natural sources have also been used as therapeutic agents for humans 15 and their antibacterial, antifungal and anticancer activities make these compounds attractive for further derivatization and for screening as therapeutic agents 16 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, plants which contain coumarins as major constituents have been used for the treatment of inflammation and other skin diseases in traditional folk medicine (Bae, 1999;Kwon et al, 2011). Recently, some natural and synthetic coumarin derivatives have been reported to inhibit melanin biosynthesis (Liu et al, 2012;Masamoto et al, 2004;Matsuda et al, 2005).…”
Section: Introductionmentioning
confidence: 99%